PEC- Formação Universitária: um estudo sobre o significado atribuído pelos alunos-professores a sua formação - Silva, Nilton José Hirota da (2006)
This work objectives to investigate the meaning attribute to the formation gotten in superior level through the program PEC- University formation ( UNESP, PUC-SP e USP), promoted by the Secretaria Estadual de Educação de São Paulo, during the years of 2001 and 2002, by teachers who is already working in the system publish of education in state of São Paulo. Fifteen citizens had been interviewed, descendant of diverse cities of Vale do Ribeira , formed in intermediate level at the same region, carriers of a superior teaching experience of the 15 years in average. From the ideas of Huberman about the phases of professional development and of Tardiff about the relation of the teacher with different knowledge necessary its practises, we intend to offer subsidies to rethink the continued formation. Valuing the knowledge of experience, in order to interlace theory and it practises, taking in consideration the organizational work conditions and forms of the school, including here the context, the culture, in view of the professionalization on the formative processes based in permanent collaborating researth